1983
DOI: 10.1104/pp.73.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Soybean Leaf Storage Glycoprotein

Abstract: Removing the pods from soybean (Glycine max [L.] Meff. cv Wye) plants induces a change in leaf function which is characterized by a change in the leaf soluble protein pattern. The synthesis of at least four polypeptides (-27, 29, 54, and 80 also demonstrated a marked increase in the accumulation of protein within the vacuoles of these cells following pod removal. Therefore, the polypeptides that accumulate following depodding may be localized in these cells.The purpose of this study was to further character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
105
3
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(118 citation statements)
references
References 9 publications
9
105
3
1
Order By: Relevance
“…), a glycoprot-ein has also been identified that accumulates markedly when reproductive sink demand is lowered by depodding (26). However, soybean VSP3 appears to be distinct from the major seed lectin of soybean (23,27). Peptide sequences derived from nucleic acid sequences ofthe VSP subunits indicate only limited homology with soybean agglutinin (23), and no hemagglutinating activity has been reported for the purified protein.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…), a glycoprot-ein has also been identified that accumulates markedly when reproductive sink demand is lowered by depodding (26). However, soybean VSP3 appears to be distinct from the major seed lectin of soybean (23,27). Peptide sequences derived from nucleic acid sequences ofthe VSP subunits indicate only limited homology with soybean agglutinin (23), and no hemagglutinating activity has been reported for the purified protein.…”
mentioning
confidence: 99%
“…Some of these glycoproteins are immunologically similar to the seed lectins isolated from the same species (6,27), but others appear to be immunologically distinct from any seed protein (for reviews, see refs. 6, 12, 14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vol. 107,1995 proteins (Mason et al, 1988;Mason and Mullet, 1990) revealed that they were identical with the soybean leaf VSPs (Wittenbach, 1983).…”
mentioning
confidence: 99%
“…17) Soybean VSPs accumulate transiently in developing organs, especially immature leaves or pods, and then decrease in content with seed maturation. 18) Increasing numbers of reports of VSPs in various plants have indicated that in woody perennials they relate to dormancy and respond to outer stimuli, such as photoperiod, chilling-accumulation, and wounding, as well as to the effects of sugar, nitrogen, and auxins.…”
mentioning
confidence: 99%